Response to Jeff Dolven. - Izenberg, Oren (Modern Philology, 2007)
The article responds to the preceding essay by Jeff Dolven on the style of 16th-century English poet Sir Thomas Wyatt. The author focuses in particular on Dolven's account of poetic style, which he contrasts with accounts in other articles in the issue, especially one on the poetry of Frank O'Hara by Maureen N. McLane.